1994
DOI: 10.1161/01.res.74.5.839
|View full text |Cite
|
Sign up to set email alerts
|

Restricted distribution of connexin40, a gap junctional protein, in mammalian heart.

Abstract: Connexin40 (Cx40) is a member of the connexin family of gap junction proteins. Its mRNA, abundant in lung, is also present in mammalian heart, although in lower amount. Rabbit antipeptide antibodies directed to the COOH terminus (residues 335 to 356) of rat Cx40 were characterized to investigate the distribution of Cx40 in rat and guinea pig cardiac tissues. The affinity-purified antibodies detect specifically a major protein (Mr, 40000) in immunoblots of total extracts from rat lung and rat and guinea pig hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
1
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(117 citation statements)
references
References 56 publications
5
110
1
1
Order By: Relevance
“…In adult mouse and rat hearts CX40 was shown to be expressed in the His bundle and the bundle branches (Gros et al, 1994. The present study demonstrates that CX40 is already expressed at 14 dpc in the early differentiating bundle branches on both sides of the growing interventricular septum.…”
Section: Distribution Of Cx40 In the Conduction Systemsupporting
confidence: 58%
See 1 more Smart Citation
“…In adult mouse and rat hearts CX40 was shown to be expressed in the His bundle and the bundle branches (Gros et al, 1994. The present study demonstrates that CX40 is already expressed at 14 dpc in the early differentiating bundle branches on both sides of the growing interventricular septum.…”
Section: Distribution Of Cx40 In the Conduction Systemsupporting
confidence: 58%
“…In addition, in the adult rat and mouse, CX43 is also absent from the ventricular conduction tissue, i.e., the His bundle and the proximal part of the bundle branches (Van Kempen et al, 1991;Gourdie et al, 1992). Interestingly, CX40 distribution studies (Gourdie et al, 1993;Gros et al, 1994Gros et al, , 1995Van Kempen et al, 1995) showed that CX40 has a more restricted distribution than CX43 in adult mammalian hearts. These authors demonstrated that (2x40 is expressed not only in atria (depending on the species) but also in ventricular conduction system myocytes.…”
mentioning
confidence: 99%
“…The difference in yi(main state) between Cx4O and Cx4O*43El,2 channels was surprising, since both connexins presumably possessed the same four transmembrane domains Ml-M4. In the case of heterotypic (Bruzzone et al, 1993) and human HeLa cells (Elfgang et al, 1995 surrounding working myocardium expresses Cx43 (Bastide et al, 1993;Gros et al, 1994 (Elfgang et al, 1995 Figure 3C). Previously, it had been shown that each immunofluorescent signal on contacting membranes of primary hepatocytes coincided with a gap junctional plaque (Dermietzel et al, 1987).…”
Section: Docking and Formation Of Heterotypic Gap Junctionsmentioning
confidence: 99%
“…This functional incompatibility is likely to contribute to the preferential propagation of action potentials along the bundles of murine conductive myocardiocytes (expressing Cx4O) which are surrounded by the working myocardium (expressing Cx43; Bastide et al, 1993;Gros et al, 1994). As yet, the molecular determinants causing the incompatibility between Cx4O and Cx43 hemichannels were not known.…”
Section: Introductionmentioning
confidence: 99%
“…Cx40, Cx43 and Cx45 are the most abundant connexin isoforms of the working mammalian myocardial cells and the conduction system. Cx40 is mainly expressed in the atrium and in the conduction system [44][45][46][47][48][49], while Cx43 can be found both in atrial and ventricular cells but not in sinoatrial and atrioventricular nodes [46,[48][49][50][51][52][53][54][55]. Cx45 is preferentially expressed in sinoatrial and atrioventricular nodes, His-bundle and bundle branches [56][57][58].…”
Section: The Distribution Of Gap Junctionsmentioning
confidence: 99%